Glutamic acid-113 serves as the retinylidene Schiff base counterion in bovine rhodopsin. - Sakmar, T P (1989)
The characteristic wavelength at which a visual pigment absorbs light is regulated by interactions between protein (opsin) and retinylidene Schiff base chromophore. By using site-directed mutagenesis, charged amino acids in bovine rhodopsin transmembrane helix C were systematically replaced. Substitution of glutamic acid-134 or arginine-135 did not affect spectral properties. However, substitution of glutamic acid-122 by glutamine or by aspartic acid formed pigments that were blue-shifted in light absorption (lambda max = 480 nm and 475 nm, respectively). While the substitution of glutamic acid-113 by aspartic acid gave a slightly red-shifted pigment (lambda max = 505 nm), replacement by glutamine formed a pigment that was strikingly blue-shifted in light absorption (lambda max = 380 nm). The 380-nm species existed in a pH-dependent equilibrium with a 490-nm species such that at acidic pH all of the pigment was converted to lambda max = 490 nm. We conclude that glutamic acid-113 serves as the retinylidene Schiff base counterion in rhodopsin. We believe that this opsin-chromophore interaction is an example of a general mechanism of color regulation in the visual pigments.